The Black Scholes Call Option Pricing Model and the Australian Options Market: Where are We after 15 Years - Frino, A; Lodh, S C; Khan, E (The International Journal of Accounting and Business Society, 1993)
The Black Scholes model has not been tested in Australia for about 10 years implying tests previously carried out used data from a developing options market. This study carries out cross sectional tests of the model using the most recent data available. The conclusion, unlike earlier studies, is that the Black Scholes model cannot be rejected, and thus that the market is efficiently pricing options in an unbiased manner (in a Black Scholes sense), or alternatively, that model is capable of effectively pricing options. A unique time series analysis of mispricing is also carried out in order to determine whether this can be attributed to a ‘market learning effect’ over time. There is some evidence of such an effect. The tests differ from those of previous studies in a number of ways. One of the major limitations of past studies is overcome as the tests do not depend on historical measures of volatility. Special care is taken to exclude possible misleading observations occurring from non-synchronous share option prices. The effects of dividends and the possibility of early exercise are dealt with by exclusion. Controls are also used to limit the possibility of incompatible risk free interest rate proxies having a confounding effect on results.